An Introduction to Telecommunications Policy in Canada - Middleton, Catherine (Journal of Telecommunications and the Digital Economy, 2017)
This paper provides an introduction to telecommunications policy in Canada, outlining the regulatory and legislative environment governing the provision of telecommunications services in the country and describing basic characteristics of its market for retail telecommunications services. It was written in 2017 as one in a series of papers describing international telecommunications policies and markets published in the Australian Journal of Telecommunications and the Digital Economy in 2016 and 2017. The discussion focuses on broad trends and major players and identifies key regulations and policies in place in 2017, with information drawn primarily from regulatory and policy documents. The paper does not offer an exhaustive description of all telecommunications policy issues, markets and providers in Canada.